The Impact of Whistleblowing System Implementation Level on Company's Operational Efficiency in Indonesia Consumer Goods Sector : Mediating Role of Fraud Prevention - Shafitri, Aarum; Kitri, Mandra (Integrasi Sains Media, 2024)
Indonesia faces significant issues with fraud across various business sectors, including consumer goods, which negatively impacts operational efficiency. This highlights the need for effective fraud prevention methods to mitigate these effects. This study uses panel data regression analysis, based on annual reports and financial statements from 2019 to 2023, to examine how the implementation level of whistleblowing systems affects operational efficiency, with fraud prevention as a mediating variable, in consumer goods companies listed on the Indonesia Stock Exchange (IDX). The findings indicate that a higher level of whistleblowing system implementation significantly enhances operational efficiency. However, fraud prevention does not mediate this relationship, as the analysis shows insignificant results regarding the impact of whistleblowing systems on fraud prevention and the effect of fraud prevention on operational efficiency. This suggests that while whistleblowing systems directly improve operational efficiency, their role in fraud prevention does not significantly influence this improvement. This research contributes to the literature by demonstrating the direct positive impact of whistleblowing systems on operational efficiency in the Indonesian consumer goods sector. It also offers practical recommendations for companies to enhance their whistleblowing systems to boost operational efficiency. Additionally, the study calls for future research to explore alternative mechanisms through which whistleblowing systems impact operational efficiency beyond fraud prevention and to investigate other methods for assessing whistleblowing system implementation and fraud incidence to reduce bias.